Ідентифікація та прогнозування стаціонарних слабо формалізованих процесів з невідомими входами - Назаренко, Олександр Максимович (НТУ "ХПІ", 2015)
Розглядається проблема специфікації та ідентифікації лінійної стаціонарної моделі з невідомими входами. Моделювання невідомих входів проводиться згідно принципу мультиплікатора. Траєкторії руху введених керувань розкладаються на трендову та періодичну складові, що дозволяє розв’язати диференціальні рівняння руху в явному вигляді. Параметрична ідентифікація невідомих коефіцієнтів здійснюється методами економетрики при певних обмеженнях на елементи матриць. Апробація побудованих алгоритмів проводиться на реальних статистичних даних.

The problem specification and identification of linear stationary model with unknown inputs. Modeling the unknown inputs carried out according to the principle of the multiplier. The trajectories of the input controls are arranged on the trend and periodic components that can solve differential equations of motion explicitly. Injected controller which includes two control devices that generate the necessary additional constraints on the parameters of the system of differential equations. Parametric identification of unknown coefficients of the model is carried out by methods of econometrics, under certain restrictions on the elements of the matrices. Testing of these algorithms is carried out on the real statistics of macroeconomic dynamics.
Parametric identification Solow model of macroeconomic system
Keywords: специфікація; апробація моделі; ідентифікація; циклічний процес; specification; cyclical process; approbation model